A capitania do Siará Grande nas dinâmicas do império português: política sesmarial, guerra justa e formação de uma elite conquistadora (1679-1720) - Silva, Rafael Ricarte da (2016)
This dissertation aims to analyze the formation of a conquering elite in the captaincy of Siará Grande between 1679 and 1720, considering that the process of conquest of the captaincy was part of the political and economic conjuncture of affirmation of the domains of the Portuguese Overseas Empire, in the face of the competition presented by other Modern States from the early seventeenth century onwards. The formation of this conquering elite was based on the fraying of the relationship between the State and the society; as far as the context of war against the gentiles, the affirmation of the territorial controls and the provision of services to the Portuguese Crown allowed the social experience of the historical subjects involved to overlap the regulations imposed by the metropolis itself, as it is evident in the allotments awarded due to the participation in the just war against the gentiles, breaking the legal standards, in the arrangements of the administration of the land by the captain-generals and in the conflict between the owners of the sesmarias, local government and the judge of the sesmarias, Cristóvão Soares Reimão, in the process of measurement and demarcation of the captaincy’s land. It is advocated the hypothesis that the effective conquest of Siará Grande capitancy was fully part of the portuguese policy in a context of redefinitions of the imperial hegemonies in Europe and in the colonial areas and used the concession of benefits (mercês) – such as military ranks, distinctive titles, administrative positions and, mainly, allotments (sesmarias) – as the way to recruit the colonial agents. The documental sources of the dissertation consists of loose manuscripts from the Overseas Council (regarding the captaincies of Siará Grande, Rio Grande, Pernambuco, Maranhão e Paraíba), legislations concerning to sesmarias (Ordinances, Decrees, Licenses and Royal Charters), sesmarias letters and records of benefits (mercês) from the Torre do Tombo National Archive.